Managing the chaos: Policy challenges in a hyperinflationary environment - Andrea Boitani; Catalin Dragomirescu-Gaina; Andrea Monticini (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2025)
We delve into Venezuela's 2018-2019 hyperinflation episode to examine the policy constraints autocratic governments face during extreme economic distress. We develop a simple model that reflects dynamics in a segmented foreign exchange (FX) market and allows us to understand how media coverage may influence discretionary policy controls. Leveraging a special dataset of daily consumer prices collected by volunteers, we show that official FX manipulation allowed the government to mitigate hyperinflationary pressures by maintaining overvalued levels relative to the black-market that in turn helped anchor expectations. Crucially, our empirical results indicate that media coverage significantly constrained the government's ability to manipulate official FX rates, despite ample reserves and a de facto control over hard currency supply. The findings offer new evidence that, even in low-accountability regimes, policy discretion is limited by media-driven scrutiny.
Keywords: D80; E31; E50; H50; P20; 330; hyperinflation; media coverage; exchange rate; policy discretion; autocratic regime